2014
DOI: 10.1007/s10103-014-1665-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic effects of zinc phthalocyanines on intracellular amastigotes of Leishmania amazonensis and Leishmania braziliensis

Abstract: This study investigated the photoactivity of four zinc phthalocyanines (PcZns) on a murine macrophage cell line infected with Leishmania amazonensis or Leishmania braziliensis. Infected and uninfected cells were incubated with PcZns at different concentrations (1-10 μM) for 3 h and then exposed to an LED device in continuous wave mode at 660 nm with a fluency of 50 J/cm(2) (25 mV). Enzymatic activity was determined by MTT assay 24 h after light treatment. The results demonstrated that all PcZns exhibited high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…In addition, cells infected with L. braziliensis were more sensitive to the treatment than cells infected with L. major, a result similar to the one observed by Oliveira and collaborators (2015), who recorded a higher efficacy of the therapy for promastigotes of L. braziliensis than for those of L. amazonensis [18]. This finding is positive for countries in South America, especially Brazil, where the L. braziliensis is the main species responsible for CL cases.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, cells infected with L. braziliensis were more sensitive to the treatment than cells infected with L. major, a result similar to the one observed by Oliveira and collaborators (2015), who recorded a higher efficacy of the therapy for promastigotes of L. braziliensis than for those of L. amazonensis [18]. This finding is positive for countries in South America, especially Brazil, where the L. braziliensis is the main species responsible for CL cases.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we tried to interpret the mechanisms that resulted in the death of these cells, considering the potential of the mitochondrial membrane and the internalization of curcumin in the evaluated macrophages. While there is a considerable number of in vitro studies that involve the application of PDT in Leishmania promastigotes, especially using photosensitizers such as methylene blue and different phthalocyanines [15][16][17][18][19][20][21], the literature involving the application of PDT with curcumin is scarce, especially when it comes to assays with infected macrophages. Such a model is closer to the expected in clinical applications and in vivo, being an important contribution to the knowledge in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Leishmania PDT has been assessed experimentally in vivo in different animal models of CL and in vitro in infected macrophages. More recent work includes the use of different photosensitizers, e.g., hypericin, phthalocyanines, phenothiazines, methylene blue, and zinc oxide, as such or after PEGylation or in liposome-/nanoparticle-encapsulated forms, to generate ROS by illumination using different light sources, e.g., light-emitting diodes (LED), lasers, and sunlight (9)(10)(11)(12)(13)(14)(15)(16)(17). The intrinsic susceptibilities of both stages of Leishmania, i.e., promastigotes and amastigotes, to PDT has been examined in that context but rarely has been explored at the cellular and molecular levels.…”
mentioning
confidence: 99%
“…Indeed, Vianna and cols [104] demonstrated that photo-inactivated parasites used as vaccine may modulate the immune response of susceptible BALB/c mice, and prophylactics protecting them against challenging infections [104]. Table 5 shows the details of the parameters and results used in the studies related to PDT and cutaneous leishmaniasis [102,103,104,105,106,107,108,109].…”
Section: Cutaneous Leishmaniasismentioning
confidence: 99%